2010
DOI: 10.1590/s0104-11692010000500012
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Vaginal Flora in Low-Risk Pregnant Women Cared for by a Public Health Service: prevalence and Association with Symptoms and Findings from Gynecological Exams

Abstract: This study identifies the prevalence of vaginal flora alterations in low-risk pregnant women and their association with reported symptoms and gynecological exams. This quantitative, descriptive, cross-sectional study was conducted in public primary care service units Considering undesirable maternal and perinatal outcomes and feasible laboratory practices, the establishment of a routine for diagnosing vaginal flora alterations in low-risk pregnant women is suggested. Los datos apuntan elevada prevalencia de l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 15 publications
1
9
0
10
Order By: Relevance
“…Some comparative studies showed that the pregnant women with trichomoniasis have 30% higher risk of delivering baby with low birth weight or delivering preterm than those without the infection (26). Also more prevalence of some STIs has been reported from pregnant women in some areas (11,29); alteration of vaginal flora during pregnancy may be of relevant consecutive concerns (30). These indicate the importance of trichomoniasis in this group of women.…”
Section: Discussionmentioning
confidence: 99%
“…Some comparative studies showed that the pregnant women with trichomoniasis have 30% higher risk of delivering baby with low birth weight or delivering preterm than those without the infection (26). Also more prevalence of some STIs has been reported from pregnant women in some areas (11,29); alteration of vaginal flora during pregnancy may be of relevant consecutive concerns (30). These indicate the importance of trichomoniasis in this group of women.…”
Section: Discussionmentioning
confidence: 99%
“…Boatto et al (2007) em seu estudo aborda que os sinais e sintomas clínicos mais relevantes na CVV foram prurido e corrimento, seguidos por eritema e edema. Os achados de Gondo et al (2010) apontam elevada prevalência das alterações de flora vaginal, com pouca associação à sintomatologia, mas associação com achados do exame ginecológico. Outro ponto relevante para este estudo é sobre as orientações prestadas às participantes.…”
Section: Discussionunclassified
“…Consistent with other research the affected age group is the younger population who are at risk for sexually transmitted infections. In a study from Brazil the mean affected age is 25 years [9].…”
Section: Discussionmentioning
confidence: 99%